Relationship Between The Level Of Knowledge And Practice In The Care Of The Administration Of Magnesium Sulphate, In Cases Of Preeclampsia And Eclampsia In Emergency Nurses And Maternal Intensive Care - Garcilazo-Lazo, Ana María (2017)
Objective. To determine the relationship level of knowledge and care practices in the administration of magnesium sulfate in cases of pre-edampsia and eclampsia. Material and methods. Analytical and descriptive study. The sample was 15 Intensive Care Nurses (UCIM) and 20 Emergency nurses. The technique was the survey and direct observation. The instruments a questionnaire and a checklist. The questionnaire was applied in monthly meeting of each service, the checklist was made through two direct observations in each shift. The statistical validity of the questionnaire was subjected to the Kuder Richarson test and the checklist was subjected to the item-test using the Pearson correlation coefficient. The data collection was June and October 2013, the processing was manual by a system of paloteo to an encoded matriz table.